HUBUNGAN ANTARA MODEL LEARNING CYCLE 7E DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA SEKOLAH DASAR: SEBUAH STUDI LITERATUR - Ayu, Dwi Hadita; Judijanto, Loso; Hendrilia, Yudi; Ramadhona, Rossa; Prananda, Gingga (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to analyze the relationship between the application of the 7E Learning Cycle model and improving elementary school students' critical thinking skills through literature study. Using the literature study method, this research examines publications from relevant national and international journals, focusing on the keywords "7E Learning Cycle Model" and "Primary School Students' Critical Thinking Skills." The research results show that the Learning Cycle 7E model is an effective learning approach in improving students' critical thinking skills. Through each stage, students are given the opportunity to explore, analyze and evaluate information in depth. Interactive activities and the use of relevant learning media support the development of skills needed to face future challenges. This research emphasizes the importance of implementing the 7E Learning Cycle model in the educational curriculum, creating a collaborative and constructivist learning environment, so that students are better prepared to become critical thinkers who contribute positively to society